Soil Characteristics Using Borelogs Database For Penang Island - Azman, Intan Halawati Syamimi Nor (Universiti Sains Malaysia, 2021)
Geographic Information System (GIS) is capable of integrating, analysing, and managing data and associated attributes and displaying geographically referenced information, which are spatially referenced to the Earth. GIS also allows to combine various maps and remote sensing information to generate models which are used in real time environment. Therefore, GIS software is capable to develop the soil map based on the Site Investigation reports in Penang Island for this research. This research aim is to determine the distribution of soil in Penang Island retrieved from secondary data. The soil data were categorised into 13 classes type of soil and 10 group of number of blows (SPTN) to develop the soil map for Penang Island. Kriging and Natural Neighbor interpolation method were used to develop the soil mapping of soil type and SPT-N map of Penang Island. The results of the mapping demonstrate that Sand is the most abundant type of soil at depths of 5 to 10 metres, covering for 44% to 40% of the total area of Penang Island. This is validated by the data collected and the mapping, which shows that Silty Sand makes up more than 31% of the soil type at 5-meter level and more than 30% at 10-meter level. Gravel and Granite make up the majority between 15 and 30 metres, accounting for 46% to 55% of Penang's total area. This supported by data gathered and mapping at a depth of 15 metres, which shows that Granitic rock makes up more than 45% of the subsurface, and from 20 metres to 30 metres where Granite covers more than half of the region. This will ease the engineers and policy makers make appropriate planning and implementation in the future development on Penang Island.